2020
DOI: 10.1002/cne.25001
|View full text |Cite
|
Sign up to set email alerts
|

Ocular dominance plasticity: Molecular mechanisms revisited

Abstract: Ocular dominance plasticity (ODP) is a type of cortical plasticity operating in visual cortex of mammals that are endowed with binocular vision based on the competition-driven disparity. Earlier, a molecular mechanism was proposed that catecholamines play an important role in the maintenance of ODP in kittens. Having survived the initial test, the hypothesis was further advanced to identify noradrenaline (NA) as a key factor that regulates ODP in the immature cortex. Later, the ODPpromoting effect of NA is ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 293 publications
(487 reference statements)
2
3
0
Order By: Relevance
“…The ODI of tested Area 17 neurons is 0.15 6 0.06 (Fig. 2E; n = 26), consistent with previous studies (Hubel and Wiesel, 1962;Wiesel and Hubel, 1963;Kara and Boyd, 2009;Kasamatsu and Imamura, 2020) showing a binocular-driven feature. The interocular transferability test consists of several steps.…”
Section: Short-term Bidirectional Plasticity Induced By Biasedadaptat...supporting
confidence: 91%
See 2 more Smart Citations
“…The ODI of tested Area 17 neurons is 0.15 6 0.06 (Fig. 2E; n = 26), consistent with previous studies (Hubel and Wiesel, 1962;Wiesel and Hubel, 1963;Kara and Boyd, 2009;Kasamatsu and Imamura, 2020) showing a binocular-driven feature. The interocular transferability test consists of several steps.…”
Section: Short-term Bidirectional Plasticity Induced By Biasedadaptat...supporting
confidence: 91%
“…Previous literature has shown that the orientation-adaptation effect could transfer interocularly in cat Areas 17 and 18 (Maffei et al, 1986). Considering that neurons in Areas 17 and 18 are mainly binocularly driven (Hubel and Wiesel, 1962;Maffei et al, 1986;Kasamatsu and Imamura, 2020), whereas LGN neurons are monocularly driven (Sanderson, 1971;LeVay and Ferster, 1977;Weyand, 2016;Ghodrati et al, 2017), interocular transferability supports the cortical origin hypothesis of orientation adaptation.…”
Section: Short-term Bidirectional Plasticity Induced By Biasedadaptat...supporting
confidence: 71%
See 1 more Smart Citation
“…A prominent view that behaviorally salient events evoke diffuse ACh release across the cortex has recently been challenged by imaging experiments that used these indicators to show heterogeneous patterns across cortical regions correlating with behavioral states and locomotion (Lohani et al, 2022). In the visual cortex, cholinergic signaling is involved in ocular dominance plasticity (Kasamatsu & Imamura, 2020) and required to encode spatiotemporal sequences (Gavornik & Bear, 2014) and intervals (Chubykin et al, 2013). While microdialysis has shown that visual stimulation can increase ACh levels in the visual cortex of anesthetized rats (Laplante et al, 2005), the extent to which this occurs during passive viewing in awake animals, and the spatiotemporal granularity of release, are unknown.…”
Section: Mainmentioning
confidence: 99%
“…These studies have demonstrated that the maturation of specific inhibitory circuits in the visual cortex is important for both opening and closing the critical period, and they have also revealed a number of “molecular brakes” that restricts plasticity after the critical period and consequently approaches to “reopening” the window of plasticity in adulthood (Stryker and Lowel, 2018 ). It is beyond the scope of this article to provide a comprehensive review of molecular and synaptic mechanisms of OD plasticity and critical period regulation, on which there are plenty in recent publications (Espinosa and Stryker, 2012 ; Hensch and Quinlan, 2018 ; Hooks and Chen, 2020 ; Kasamatsu and Imamura, 2020 ; Xu et al, 2020a ). We will therefore limit our discussion to two issues of OD that are the most relevant to binocular vision.…”
Section: Ocular Dominance and Its Plasticitymentioning
confidence: 99%